Thermodynamic and thermal properties of the C60-l-Arg derivative. (December 2018) - Iurev, Gleb O.; Lelet, Maxim I.; Pochkaeva, Evgeniia I.; Petrov, Andrey V.; Semenov, Konstantin N.; Charykov, Nikolay A.; Podolsky, Nikita E.; Dulneva, Larisa L.; Sharoyko, Vladimir V.; Murin, Igor V.
Highlights: Heat capacities of C60 -Arg derivative were measured between T = 5 K and T = 328 K. Standard thermodynamic functions of crystalline C60 (C6 H14 N4 O2 )8 were calculated over the range from T → 0 to 320 K. DFT simulated data on temperature dependence of heat capacity for C60 -Arg derivative are presented. Abstract: The paper presents experimental and DFT simulated data on temperature dependence of heat capacity for C60 -l -arginine derivative. Smoothed C p, m ∘ T values in the temperature range from T  → 0 K to 320 K are presented along with the values of standard thermodynamic functions: S m °, [ H m ∘ T - H m ∘ 0 ] and [ Φ m ∘ T - Φ m ∘ 0 ]. In addition, the molar third law entropy and the molar formation entropy of the C60 -l -arginine derivative in crystalline state at T  = 298.15 K are calculated. The data on complex thermal analysis reveal that the C60 -l -arginine derivative is stable up to 340 K. Further increasing of temperature leads to destruction ofl -arginine groups and oxidation of fullerene core.